Letter from Eugène Lemercier to his mother, Marguerite Lemercier, giving her general news and his impressions - Lemercier, Eugène Emmanuel, 1886-1915; Lemercier, Marguerite, 1859-ca. 1930 (1914)
Mentions a godfather, Rummel, Corilla, Marie Louise [probably his mother's maid], Charles R[app] and Sordes. Describes his night job and his companions("brutes"). Mentions philosophers Maeterlinck and Bergson and wonders how can the Germans hate when they have written such great music. Also mentions the Poirson competition.
Addressed to "Madame Lemercier / 40 Rue Lauriston 40 / Paris". No postmark.
Inscription "correspondance militaire" above the address.
Also partially published in Lettres d'un soldat (août 1914-avril 1915) : Présentées par Bernard Giovanangeli / Eugène Emmanuel Lemercier. Paris : Bernard Giovanangeli Editeur, 2013.
Lettres d'un soldat (août 1914-avril 1915) : Préface de André Chevrillon / [Eugène Lemercier]. Paris : Librairie Chapelot, 1916.
Keywords: Lemercier, Eugène Emmanuel, -- 1886-1915 -- Correspondence; Bergson, Henri, -- 1859-1941; World War, 1914-1918 -- France; World War, 1914-1918 -- France -- Correspondence; France -- History -- 1914-1940